Seismic performance of masonry cross vaults through shaking table testing on a scaled model - Bianchini, Nicoletta (2021)
Masonry cross vaults are among the most widely used typologies of horizontal structural elements for covering spaces of both ordinary and monumental buildings in the European countries. Their seismic vulnerability has been proved by systematic damages and collapses surveyed throughout the centuries. Therefore, the assessment of their structural safety is a crucial issue for the conservation and preservation of historical buildings. Although various methods have been developed and used to analyse both the stability (e.g. equilibrium method) and the dynamic behaviour (e.g. finite and discrete element approaches) of vaulted structures, experimental studies are constantly needed to validate and calibrate models. In this regard, limited experimental studies to understand the dynamic response of vaults have been done. The present paper describes the results of shake table tests on a 1:5 scaled cross vault model made of 3D printed blocks assembled with dry joints, carried out at the 3D LNEC shake table (Portugal). The main aim of the tests is to investigate one of the most typical seismic damage for cross vaults: the shear failure. This type of mechanism frequently affects vaults of lateral aisles and it is mainly caused by a significant difference in stiffness of vaults’ supports. Indeed, the lower stiffness of the central nave colonnade compared to the external wall may induce an in-plane shear distortion of the vault caused by a differential longitudinal displacement of its opposite sides. Incremental seismic motions are conducted up to collapse using Emilia Romagna earthquake. The results are analysed in terms crack pattern and damage mechanisms.